Rancang Bangun Website Media Promosi Sekolah dan Pengembangan PPDB dengan Metode User Centered Design - Indah Ayu Wijayanti; Nurahman - (LPPM UBHINUS MALANG, 2023)
SMP Negeri 8 Sampit is a school located on Jalan Jendral Sudirman Km.6.5, Pasir Putih Village, Mentawa Baru District, Ketapang. One of the benefits of technology used by the school is as a medium for school promotion and in the New Student Admission (PPDB) process. Currently, media promotion at SMP Negeri 8 Sampit is still being carried out through written media such as brochures, banners or bulletin boards. Dissemination of information conventionally has limited reach and time in disseminating information. While the PPDB process is carried out by recording the data of prospective students on paper and then the data is processed using Microsoft Excel. This has an impact on data processing for the announcement of the acceptance of the selection results which takes a long time. In addition, the accumulation of physical files is prone to damage. In this study, a school website was created using the User Centered Design (UCD) method and evaluated by blackbox. The existence of this website has answered the research objectives, namely making it easier for schools to disseminate information to the wider community and making it easier for the committee to manage PPDB files quickly and efficiently. System evaluation carried out using blackbox resulted in website functions being appropriate and running well when used.